2003
DOI: 10.1103/physreve.67.021112
|View full text |Cite
|
Sign up to set email alerts
|

Continuous-time random-walk model for financial distributions

Abstract: We apply the formalism of the continuous-time random walk to the study of financial data. The entire distribution of prices can be obtained once two auxiliary densities are known. These are the probability densities for the pausing time between successive jumps and the corresponding probability density for the magnitude of a jump. We have applied the formalism to data on the U.S. dollar-deutsche mark future exchange, finding good agreement between theory and the observed data.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
133
0
2

Year Published

2004
2004
2014
2014

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 175 publications
(139 citation statements)
references
References 23 publications
3
133
0
2
Order By: Relevance
“…Several researchers have recently investigated the statistical properties of waiting times of high-frequency financial data [17][18][19][20][21][22][23][24], and Scalas et al [17][18][19][20][21] in particular have applied the theory of continuous time random walk (CTRW) to financial data. They also found that the waiting-time survival probability for high-frequency data of the 30 DJIA stocks is non-exponential [21].…”
Section: Introductionmentioning
confidence: 99%
“…Several researchers have recently investigated the statistical properties of waiting times of high-frequency financial data [17][18][19][20][21][22][23][24], and Scalas et al [17][18][19][20][21] in particular have applied the theory of continuous time random walk (CTRW) to financial data. They also found that the waiting-time survival probability for high-frequency data of the 30 DJIA stocks is non-exponential [21].…”
Section: Introductionmentioning
confidence: 99%
“…email and short message sending, online clicking of web pages, making calls, financial commerce, etc.) follow power-law distribution (Barabási 2005;Dezso et al 2006;Han et al 2008;Masoliver et al 2003). The results indicate that for human activities, instead of pure random processes, there might be more underlying principles.…”
Section: Timing Characteristics Of Research Interestsmentioning
confidence: 77%
“…However, there is a large number of natural and industrial processes that involve non-exponential waiting times. [27][28][29][30] For example, coupling of mechanical degrees of freedom with chemical processes in motor proteins might lead to non-exponential waiting time distributions. 28 More generally, when a given state has an internal structure, for instance, a smaller sub-network of states, we should expect non-exponential dwell time distributions and violations of the Markov property.…”
Section: Introductionmentioning
confidence: 99%